Variable resistance of RMS to interferon γ signaling - Simon-Keller, Katja; Mößinger, Katharina; Bohlender-Willke, Anna-Lena; Ströbel, Philipp; Marx, Alexander (ISRN oncology, 2012)
Aims. Chimeric T cells directed to the γ-subunit of the fetal acetylcholine receptor (fAChR) produce large amounts of interferon-γ (IFNγ) on coculture with fAChR-expressing rhabdomyosarcoma (RMS) cells prior to RMS cell death. The aim of this study was to elucidate whether IFNγ blocks proliferation and survival of RMS cells and modulates expression of genes with relevance for cytotoxicity of chimeric T cells. Methods. Expression levels of IFNγ receptor (IFNGR), AChR, MHCI, MHCII, and CIITA (class II transactivator) by RMS were checked by flow cytometry, qRT-PCR, and western blot. Proliferation and cell survival were investigated by annexin V and propidium iodide staining and MTT (thiazolyl-blue-tetrazolium-bromide) assay. Key phosphorylation and binding sites of IFNGRs were checked by DNA sequencing. Results. IFNγ treatment blocked proliferation in 3 of 6 RMS cell lines, but reduced survival in only one. IFNGR was expressed at levels comparable to controls and binding sites for JAK and STAT1 were intact. Induction of several target genes (e.g., AChR, MHCI, and MHCII) by IFNγ was detected on the RNA level but not protein level. Conclusions. IFNγ does not significantly contribute to the killing of RMS cells by fAChR directed chimeric T cells. Signalling downstream of the IFNR receptor, including the posttranscriptional level, is impaired in most RMS cell lines.
Gesehen am 16.10.2018